Security Region of Integrated Heat and Electricity System Considering Thermal Dynamics - Long, Zhuhua; Zhang, Shiqiang; He, Wenfeng (Frontiers in Energy Research, 2022)
The broad development of integrated heat and electricity systems (IHES) improved the energy utilization efficiency, but it also increased the risk of cascaded accidents and the difficulty of operation. The security region that defines the permitted operation range is efficient for the planning and control of IHESs, while the accurate formulation of security region boundary renders its applications. To address this problem, this article first proposes a novel equivalent thermal model (ETM) to build the direct connection between the operations states and the control variables in the heating system. The ETM directly characterizes the network response to the inputs and accurately describes the dynamic process in the heat system. On this basis, the method to construct the security region for IHES is presented considering the thermal dynamics, where the critical boundary is formulated with a set of accurate hyperplanes. To describe the thermal dynamics, numerical simulations from different aspects verify the effectiveness of the ETM. The results of security region indicate that the thermal dynamics influence the operation security and renewable penetration in the power system significantly.